Low-density lipoprotein receptor-related protein 1 (LRP1) is a novel receptor for apolipoprotein A4 (APOA4) in adipose tissue - Jie Qu (Nature Portfolio, 2021)
Abstract Apolipoprotein A4 (APOA4) is one of the most abundant and versatile apolipoproteins facilitating lipid transport and metabolism. APOA4 is synthesized in the small intestine, packaged onto chylomicrons, secreted into intestinal lymph and transported via circulation to several tissues, including adipose. Since its discovery nearly 4 decades ago, to date, only platelet integrin αIIbβ3 has been identified as APOA4 receptor in the plasma. Using co-immunoprecipitation coupled with mass spectrometry, we probed the APOA4 interactome in mouse gonadal fat tissue, where ApoA4 gene is not transcribed but APOA4 protein is abundant. We demonstrate that lipoprotein receptor-related protein 1 (LRP1) is the cognate receptor for APOA4 in adipose tissue. LRP1 colocalized with APOA4 in adipocytes; it interacted with APOA4 under fasting condition and their interaction was enhanced during lipid feeding concomitant with increased APOA4 levels in plasma. In 3T3-L1 mature adipocytes, APOA4 promoted glucose uptake both in absence and presence of insulin in a dose-dependent manner. Knockdown of LRP1 abrogated APOA4-induced glucose uptake as well as activation of phosphatidylinositol 3 kinase (PI3K)-mediated protein kinase B (AKT). Taken together, we identified LRP1 as a novel receptor for APOA4 in promoting glucose uptake. Considering both APOA4 and LRP1 are multifunctional players in lipid and glucose metabolism, our finding opens up a door to better understand the molecular mechanisms along APOA4-LRP1 axis, whose dysregulation leads to obesity, cardiovascular disease, and diabetes.